PERAN KOMPOSTER DALAM PENYEIMBANG LINGKUNGAN AKIBAT DAMPAK PENUMPUKAN SAMPAH ORGANIK WARGA - Putra, Heristama; Finsensia Riti, Yosefina; Alesandro Santosa, Hosea; Christopher, Jeremy (Institut Keuangan-Perbankan Dan Informatika Asia Perbanas, 2026)
One of the biggest problems caused by waste also stems from the increasing number of immigrants from year to year, resulting in an increase in the city's population. Furthermore, it is also a result of the economic cycle of residents who daily require primary necessities such as food and drink to sustain life. The large amount of household organic waste can cause accumulation in the TPS (Temporary Disposal Site) area and, if left untreated, can become a source of disease in the environment. A good environment is expected to prevent its residents from a slum atmosphere and ensure the health of its residents. Currently, in the Babatan Pilang Housing area, especially in the RT.002 area, the amount of daily waste produced by residents is very large, requiring additional management to reduce the volume of waste. By using the vertical culture method, the community service team, together with residents, collaborated to create several composters as an additional alternative for storing household organic waste. The implementation of this method has been carried out from the beginning, starting from mentoring, implementation, monitoring, and evaluation of all community service activities that have been carried out. So the expected result is that the existence of the composter can be an alternative for disposing of household organic waste through a natural decomposition process in the soil. The results of this decomposition can later be developed to produce compost fertilizer which can be used well for sowing/fertilizing all plants in the surrounding environment.